Kinetic Processes in Amorphous Materials Revealed by Thermal Analysis: Application to Glassy Selenium - Málek, Jiří; Svoboda, Roman (MDPI, 2019)
It is expected that viscous flow is affecting the kinetic processes in a supercooled liquid, such as the structural relaxation and the crystallization kinetics. These processes significantly influence the behavior of glass being prepared by quenching. In this paper, the activation energy of viscous flow is discussed with respect to the activation energy of crystal growth and the structural relaxation of glassy selenium. Differential scanning calorimetry (DSC), thermomechanical analysis (TMA) and hot-stage infrared microscopy were used. It is shown that the activation energy of structural relaxation corresponds to that of the viscous flow at the lowest value of the glass transition temperature obtained within the commonly achievable time scale. The temperature-dependent activation energy of crystal growth, data obtained by isothermal and non-isothermal DSC and TMA experiments, as well as direct microscopic measurements, follows nearly the same dependence as the activation energy of viscous flow, taking into account viscosity and crystal growth rate decoupling due to the departure from Stokes-Einstein behavior.
Kinetické procesy v amorfních materiálech sledované pomocí termální analýzy: Aplikace na amorfní selen
Keywords: glass; structural relaxation; crystallization; viscosity; thermal analysis; sklo; strukturní relaxace; krystalizace; viskozita; termální analýza